Flowering plants. eudicots : Malpighiales - Kubitzki, Klaus (The Families and Genera of Vascular Plants, 2014)
This volume presents systematic treatments for the families and genera of the Malpighiales, which more recently have been recognised as a new major group of the eudicots. Apart from several herbaceous lineages (already treated in Vol. IX of this series), the order consists mainly of rainforest trees, particularly those of the understorey. Accompanied by other early eudicot lineages, this reflects the well-documented origin of the group as invaders into the conifer-, cycad- and seed fern-dominated forests of the Cretaceous which, at that time, were transformed into the tropical rainforest biome. In this volume, 24 families with 429 genera comprising over 12,000 species are treated. Many of these belong to the vast family of the Euphorbiaceae (here conceived in a broader sense), followed by the Violaceae, whereas some of the remaining families are very small and even relictual. The revised classification includes a complete inventory of the genera belonging to the families treated in this volume, along with their diagnostic features and keys for their identification. References to the latest taxonomic literature and links to many different disciplines important to modern plant systematics make the volume a valuable source of information on the manifold aspects of plant diversity.